Research methods for business : a skill-building approach - Sekaran, Uma; Bougie, Roger (Wiley, 2013)
Research Methods for Business: A Skill-Building Approach is a concise and straightforward introduction for students to the world of business research. The skill-building approach provides students with practical perspectives on how research can be applied in real business situations